An analysis of the prevalence of children with disabilities and disabling chronic illnesses in the Western health sub-district of Cape Town, and the services available for them - Redfern, Andrew William (Department of Paediatrics and Child Health, 2015)
Children with disabling chronic illnesses are known to have complex and frequently unmet health care needs. Limited information exists in South Africa regarding the prevalence of children with disability, as well their needs and utilization of services. The purpose of the current study is twofold: (1) identify the number of children known with disability, or disabling chronic illnesses in the western health sub-district of Cape Town; (2) analyse the health services that currently exist for these children. A period prevalence survey was conducted between January 2010 and December 2011. Numerous sources of information were sought to identify as many children with disabling chronic illness as possible. These included the referral hospitals for the Western sub-district, namely Red Cross War Memorial Children's Hospital and New Somerset Hospital, as well as the institutions where children with disability are cared for or educated, and relevant non-profit organisations in the disability sector. Information was gathered between January 2011 and Sept 2012.